Christmas journeys : a trilogy - Brown, Helen, 1956- (Rob Roy, NSW : Reading Stones Publishing, 2021)
Mary, an 86 year-old has become stuck in her ways. A journey to the past gives her a new perspective on life and faith. Her granddaughter suffers a tragedy and then embarks on a journey of her own which gives her a new hope, and mission, for the future of both her family and her country.
Prelude -- A rose of faith -- Mary's journey to love -- Susan's future hope.
Title from title screen.
Mode of Access: Available online.
Keywords: Romance; Electronic books; Christian fiction